2009
DOI: 10.1200/jco.2009.27.15_suppl.4542
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of weekly intravenous and intraperitoneal paclitaxel combined with S-1 for advanced gastric cancer with peritoneal metastasis

Abstract: 4542 Background: A phase II study to evaluate the efficacy and tolerability of weekly intravenous and intraperitoneal paclitaxel combined with S-1 was performed in gastric cancer patients with peritoneal metastasis. Methods: Gastric cancer patients with peritoneal dissemination and/or cancer cells on peritoneal cytology were enrolled. Paclitaxel was administered intravenously at 50 mg/m2 and intraperitoneally at 20 mg/m2 on days 1 and 8. S-1 was administered at 80 mg/m2/day for 14 consecutive days, followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Clinical trials showed that IP cisplatin administration improved survival of patients with peritoneal dissemination. 11 Such benefits should be further enhanced by use of hydrogels as a matrix for drug loading. Drug-loaded matrix hydrogels in the peritoneal cavity could allow sustained drug release, improving therapeutic outcomes and decreasing side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials showed that IP cisplatin administration improved survival of patients with peritoneal dissemination. 11 Such benefits should be further enhanced by use of hydrogels as a matrix for drug loading. Drug-loaded matrix hydrogels in the peritoneal cavity could allow sustained drug release, improving therapeutic outcomes and decreasing side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, important goals of treatment would be to control the development of ascites and to improve survival in patients with PDAC with peritoneal dissemination who have poor quality of life and a dismal prognosis. Compared with systemic chemotherapy, intraperitoneal chemotherapy appears to be advantageous for the treatment of peritoneal dissemination due to the high drug concentration achieved in the peritoneal cavity to directly contact tumor nodules 22‐29 . Although hyperthermic intraperitoneal chemotherapy (HIPEC), 30,31 and pressurized intraperitoneal aerosol chemotherapy (PIPAC) 32,33 have also been implemented in patients with PDAC with peritoneal dissemination, the clinical efficacy of these options in patients with PDAC is still under investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with systemic chemotherapy, intraperitoneal chemotherapy appears to be advantageous for the treatment of peritoneal dissemination due to the high drug concentration achieved in the peritoneal cavity to directly contact tumor nodules. [22][23][24][25][26][27][28][29] Although hyperthermic intraperitoneal chemotherapy (HIPEC), 30,31 and pressurized intraperitoneal aerosol chemotherapy (PIPAC) 32,33 have also been implemented in patients with PDAC with peritoneal dissemination, the clinical efficacy of these options in patients with PDAC is still under investigation. Intraperitoneal chemotherapy with paclitaxel provided a better MST of 14-16 months in a cohort of patients with occult peritoneal dissemination and of 28 months or longer in patients who underwent conversion surgery in phase II studies.…”
Section: Therapeutic Approach To Peritoneal Dissemination (Chemothera...mentioning
confidence: 99%
“…Researchers in Japan have studied repeated cycles of IP paclitaxel in patients with stage-4 gastric cancer with peritoneal involvement. 6,[13][14][15][16] These studies, including the phase-1 dose-finding study by Ishigami et al, 14 were conducted in the Japanese population. In addition, the majority of these studies used S-1 which is not available in some other parts of the world including Australia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the use of S-1 combination chemotherapy regimens which is not routinely used in some countries, many of the published reports on IP chemotherapy have been conducted in particular populations, namely Japanese or Korean patients. 6,[10][11][12][13][14][15][16] We report a phase-1 study which, for the first time, defines a recommended dose of IP paclitaxel in combination with standard systemic chemotherapy in an Australian population.…”
Section: Introductionmentioning
confidence: 99%